Platelet Accumulation on Fibrin-coated Polyethylene: Role of Platelet Activation and Factor XIII - Rubens, F D; Perry, D W; Hatton, M W C; Bishop, P D; Packham, M A; Kinlough-Rathbone, R L (Thrombosis and Haemostasis, 1995)
Platelet accumulation on small- and medium-calibre vascular grafts plays a significant role in graft occlusion. We examined platelet accumulation on the surface of fibrin-coated polyethylene tubing (internal diameter 0.17 cm) during 10 min of flow (l0ml/min) at high wall shear rate (764 s-1). Washed platelets labelled with 51Cr were resuspended in Tyrode solution containing albumin, apyrase and red blood cells (hematocrit 40%). When the thrombin that was used to form the fibrin-coated surface was inactivated with FPRCH2C1 before perfusion of the tubes with the platelet:red blood cell suspension, the accumulation of platelets was 59,840 ± 27,960 platelets per mm2, whereas accumulation on fibrin with residual active thrombin was 316,750 ± 32,560 platelets per mm2 (n = 4). When the fibrin on the surface was cross-linked by including recombinant factor XIII (rFXIII) in the fibrinogen solution used to prepare the fibrin-coated surface, platelet accumulation, after thrombin neutralization, was reduced by the cross-linking from 46,974 ± 9702 to 36,818 ± 7964 platelets per mm2 (n = 12, p <0.01). Platelet accumulation on tubes coated with D-dimer was ten times less than on tubes coated with D-domain; this finding also supports the observation that cross-linking of fibrin with the formation of γ-γ dimers reduces platelet accumulation on the fibrin-coated surface. Thrombin-activated platelets themselves were shown to cross-link fibrin when they had adhered to it during perfusion, or in a static system in which thrombin was used to form clots from FXIII-free fibrinogen in the presence of platelets. Thus, cross-linking of fibrin by FXIII in plasma or from platelets probably decreases the reactivity of the fibrin-containing thrombi to platelets by altering the lysine residue at or near the platelet-binding site of each of the γ-chains of the fibrinogen which was converted into the fibrin of these thrombi.